ZnIn2S4‐Based Nanostructures in Artificial Photosynthesis: Insights into Photocatalytic Reduction toward Sustainable Energy Production. Issue 11 (11th November 2022) - Ren, Yijie; Foo, Joel Jie; Zeng, Deqian; Ong, Wee‐Jun
Abstract : Photocatalysis for Green Energy In article number 2200017, Wee‐Jun Ong and co‐workers, exemplify the state‐of‐the‐art review of ZnIn2 S4 based‐photocatalysts in the application of CO2 reduction, N2 fixation and water splitting. A step closer to a circular carbon economy with ZnIn2 S4 ‐based photocatalysts can be achieved by harnessing sunlight toward green energy generation. The space‐themed cover art portrays the potential use of ZnIn2 S4 photocatalysts in converting greenhouse gases (CO2 ) into clean fuels via solar‐driven catalytic reactions. The crystal structures revolving around the Earth denote a representative crystal structure of photocatalysts to transform from a fossil‐based industry to a renewable‐driven sustainable process.